In regards to lipoxins as lipid mediators for the resolution of inflammation using the example of asthma - O. Yu. Kytikova; T. P. Novgorodtseva; I. S. Kovalenko (Acta Biomedica Scientifica)
Asthma is the most important medical and social problem of our time due to its widespread prevalence, chronic course and heterogeneity, which determines the complexity of  treating this disease. Chronic inflammation, characteristic of  asthma, is accompanied by the development of an imbalance between pro-inflammatory and pro-resolving lipid mediators produced by omega-3 (ω-3) and omega-6 (ω-6) polyunsaturated fatty acids (PUFAs).The  aim of  the  study. To  summarize modern ideas about the  role of  lipid mediators of inflammation resolution – lipoxins in the pathogenesis of asthma based on an analysis of articles published in English until 2023 in the PubMed database. These mediators are formed in very small quantities and are quite unstable in comparison with other lipid mediators of inflammation resolution, so the difficulty of their detection limits the study of the role of lipoxins as mediators of inflammation resolution, including in asthma. At the same time, a significant number of works have been published describing the anti-inflammatory and pro-resolving properties of lipoxins. To block the inflammatory response and trigger the processes of its resolution, lipoxins interact with the N-formyl peptide receptor type 2 and the nuclear receptor for aromatic hydrocarbons.This review discusses the controversy surrounding the role of lipoxins as pro-resolving mediators and the potential therapeutic benefits oftargeting lipoxin receptors.